Frequency of providing a palliative approach to care in family practice: a chart review and perceptions of healthcare practitioners in Canada - Gallagher, Erin; Carter-Ramirez, Daniel; Boese, Kaitlyn; Winemaker, Samantha; MacLennan, Amanda; Hansen, Nicolle; Hafid, Abe; Howard, Michelle (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Most patients nearing the end of life can benefit from a palliative approach in primary care. We currently do not know how to measure a palliative approach in family practice. The objective of this study was to describe the provision of a palliative approach and evaluate clinicians’ perceptions of the results. Methods We conducted a descriptive study of deceased patients in an interprofessional team family practice. We integrated conceptual models of a palliative approach to create a chart review tool to capture a palliative approach in the last year of life and assessed a global rating of whether a palliative approach was provided. Clinicians completed a questionnaire before learning the results and after, on perceptions of how often they believed a palliative approach was provided by the team. Results Among 79 patients (mean age at death 73 years, 54% female) cancer and cardiac diseases were the top conditions responsible for death. One-quarter of patients were assessed as having received a palliative approach. 53% of decedents had a documented discussion about goals of care, 41% had nurse involvement, and 15.2% had a discussion about caregiver well-being. These indicators had the greatest discrimination between a palliative approach or not. Agreement that elements of a palliative approach were provided decreased significantly on the clinician questionnaire from before to after viewing the results. Conclusions This study identified measurable indicators of a palliative approach in family practice, that can be used as the basis for quality improvement.